Quantitative scale validation of the Dimensional Anhedonia Rating Scale in the treatment of Chinese patients with major depressive disorder - XiaoJing Gu; Xiaowei Chen; Yun-Ai Su; Tianmei Si; Jingyu Lin; Donald M Bushnell; Dongjing Fu; Carol Jamieson; Heather Rozjabek (General Psychiatry)
Background The patient-reported Dimensional Anhedonia Rating Scale (DARS) has been adapted into Chinese, so there is a need to evaluate its measurement properties in a Chinese population.Aims To evaluate the reliability and validity of the DARS among Chinese individuals with major depressive disorder (MDD) and its treatment sensitivity in a prospective clinical study.Methods Data were from a multicentre, prospective clinical study (NCT03294525), which recruited both patients with MDD, who were followed for 8 weeks, and healthy controls (HCs), assessed at baseline only. The analysis included confirmatory factor analysis, validity and sensitivity to change.Results Patients’ mean (standard deviation (SD)) age was 34.8 (11.0) years, with 68.7% being female. 75.2% of patients with MDD had melancholic features, followed by 63.8% with anxious distress. Patients had experienced MDD for a mean (SD) of 9.2 (18) months. DARS scores covered the full range of severity with no major floor or ceiling effects. Confirmatory factor analysis showed adequate fit statistics (comparative fit index 0.976, goodness-of-fit index 0.935 and root mean square error of approximation 0.055). Convergent validity with anhedonia-related measures was confirmed. While the correlation between the DARS and the Hamilton Depression Rating Scale was not strong (r=0.31, baseline), the DARS was found to differentiate between levels of depression. Greater improvements in DARS scores were seen with the Hamilton Rating Scale for Depression responder group (effect size 1.16) compared with the non-responder group (effect size 0.46).Conclusions This study comprehensively evaluated the measurement properties of the DARS using a Chinese population with MDD. Overall, the Chinese version of DARS demonstrates good psychometric properties and has been found to be responsive to change during antidepressant treatment. The DARS is a suitable scale for assessing patient-reported anhedonia in future clinical trials.